The role of education in the determination of earnings in Poland – intergenerational differences - Sztanderska, Urszula; Grotkowska, Gabriela (Rola wykształcenia w kształtowaniu płac w Polsce − różnice międzygeneracyjne, 2019)
Recent decades have brought about a significant increase of earnings differenti in many countries. Poland is an interesting example of transformations in this regard, in particular due to the intergenerational changes of human capital resources. The aim of the article is an analysis of earnings determinants differentiation in Poland depending on the age of the employees, in particular, to what extent are the earnings differentiated by the level of education, and to what extent by the occupational record (total job tenure and at a given employer). The parameters of the Mincerian equation (1974) with the use of data derived from the Structure of Earnings Survey conducted by Central Statistical Office in 2016 were determined in the study. The results indicate that the human capital gained during the performance of professional work is of relatively small importance in comparison to the education and that this significance decreases in further age groups
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2019; vol. 63, nr 7, s. 155-171
Keywords: wages; human capital theory; education; job tenure; wynagrodzenia; teoria kapitału ludzkiego; wykształcenie; staż zawodowy